Managing Knowledge For Global And Collaborative Innovations. (World Scientific, 2009)
In today's networked and interconnected world, improving communication, collaboration and knowledge sharing between people and organization is very important. Collaboration is more than just being connected through the Internet and various forms of social networks. Collaboration through information and communication technologies requires us to "prepare the mind" for partnerships. Many of the traditional business models, organizational structures, and educational systems are not yet ready for the new forms of collaboration that go beyond organizational boundaries. Concepts like "open innovation.